SOSIALISASI PENINGKATAN KEMAMPUAN MASYARAKAT DALAM BUDIDAYA KAMBING DI GAMPONG MEUNASAH PANGGOI KECAMATAN MUARA DUA KOTA LHOKSEUMAWE - Faisal Faisal; Miswar Miswar; muhammad lutfi Al Fahmi; Rossahara Rossahara; Edi Putra (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract: Gampong's potential is all natural resources and human resources owned by Gampong as the basic capital that needs to be managed and developed for the continuity and development of Gampong. Overall, almost every resident of Gampong meunasah panggoi has livestock. The existence of goat farmers is one solution in helping stabilize the rural economy. The study of efforts to improve the ability of the community in goat cultivation aims to determine the potential resources of small-scale goat farmers related to increasing business and the ability and knowledge of farmers by providing production inputs, labor productivity and various kinds of livestock technology. The results achieved in the form of increasing the ability of the community and goat farmers formally and informally, expanding the experience of raising livestock can accelerate the increase in the basic potential and capacity of goat farmers. So it can be concluded with the efforts made, namely that farmers are increasingly able to carry out good goat cultivation methods including the layout of the cage, feed and provision of vitamins need to be done to strengthen the potential of goat farmers.Keywords: Improvement, ability, Community, Goat CultivationAbstrak: Potensi Gampong adalah segenap sumber daya alam dan sumber daya manusia yang dimiliki Gampong sebagai modal dasar yang perlu dikelola dan dikembangkan bagi kelangsungan dan perkembangan Gampong. Secara keseluruhan hampir setiap penduduk Gampong meunasah panggoi memiliki hewan ternak. Keberadaan peternak kambing menjadi salah satu solusi dalam membantu menstabilkan perekonomian pedesaan. Kajian upaya peningkatan kemampuan masyarakat dalam budidaya kambing  bertujuan untuk  mengetahui potensi sumber daya peternak  kambing skala kecil yang berhubungan dengan peningkatan usaha dan kemampuan serta pengetahuan peternak dengan penyediaan input produksi, produktivitas tenaga kerja dan berbagai macam teknologi peternakan. Hasil yang dicapai berupa peningkatan kemampuan masyarakat dan peternak kambing secara formal maupun informal, perluasan pengalaman beternak dapat mempercepat peningkatan potensi dasar dan kapasitas peternak kambing. Maka dapat disimpulkan dengan upaya yang dilakukan yaitu para peternak semakin mampu menjalankan cara pembudidayaan kambing yang baik diantaranya tata letak kandang, pakan serta pemberian vitamin perlu dilakukan untuk memperkuat potensi peternak kambing.Kata kunci: Peningkatan, kemampuan, Masyarakat, Budidaya Kambing